Triple subcellular targeting of isopentenyl diphosphate isomerases encoded by a single gene - Guirimand, Grégory (Landes Bioscience, 2012)
Isopentenyl diphosphate isomerase (IDI) is a key enzyme of the isoprenoid pathway, catalyzing the interconversion of isopentenyl diphosphate and dimethylallyl diphosphate, the universal precursors of all isoprenoids. In plants, several subcellular compartments, including cytosol/ER, peroxisomes, mitochondria and plastids, are involved in isoprenoid biosynthesis. Here, we report on the unique triple targeting of two Catharanthus roseus IDI isoforms encoded by a single gene (CrIDI1). The triple localization of CrIDI1 in mitochondria, plastids and peroxisomes is explained by alternative transcription initiation of CrIDI1, by the specificity of a bifunctional N-terminal mitochondria/plastid transit peptide and by the presence of a C-terminal peroxisomal targeting signal. Moreover, bimolecular fluorescence complementation assays revealed self-interactions suggesting that the IDI likely acts as a multimer in vivo.